P04.11 10-Year Institutional Retrospective Case Series of WHO Grade II Gliomas and Correlation of Seizures, Lobar Location, Histopathological Subtype and IDH-1 Mutation (2010–2020). (9th September 2021) - Lammy, S; Bridgman, E; Johnson, H; Taylor, A; Grivas, A
Abstract: BACKGROUND: A 10-year retrospective case series was undertaken of all patients who had a tissue diagnosis of a World Health Organisation (WHO) Grade II glioma, i.e. low grade glioma (LGGM), at the Institute of Neurological Sciences (INS) between January 2010 and January 2020 (NB: pre-2016 World Health Organisation classification). The objective was to assess the correlation of World Health Organisation (WHO) Grade II gliomas to seizure symptomology, intracerebral tumour location, histopathological glioma sub-type and molecular markers including isocitrate dehydrogenase-1 (IDH-1) mutation. MATERIAL AND METHODS: We extracted data regarding clinical, radiological, histological, molecular discriminators and functional outcomes in patients. The pre-operative symptomology was restricted to seizures, headache and focal neurological deficits. RESULTS: 84 patients underwent resection and had a mean age of 42rs (range: 21-77yrs]). Seizures (NB: pre-2017 International League against Epilepsy classification [ILAE]) occurred in 71% and of these 52% were generalised, 37% partial and 11% mixed. 31% had ongoing seizures postoperatively. Headache occurred in 38% (of these 50% had headache and seizures). Focal neurological deficits (FNDs) occurred in 21% (of these 61% had FNDs and seizures). Seizure, as an isolated pre-operative symptom occurred in 48% patients compared to isolated headache in 10% and isolated FNDs in 4%. Anatomically, 58% of lesions were frontal. The seizure spatial frequency was 60% frontal. Histologically, 60% were diffuse astrocytomas and 40% oligodendrogliomas. Furthermore, 71% of oligodendrogliomas and 49% of diffuse astrocytomas had a frontal location. IDH-1 mutation occurred in 80% patients (75% of these had seizures) and of these 66% were frontal. CONCLUSIONS: Our analysis confirms a correlation between incidence of seizures, frontal lobar location, histopathological subtype and IDH-1 mutations (p = <0.05